1998
DOI: 10.1083/jcb.143.3.767
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle–related Changes in the Conducting Properties of r-eag K+ Channels

Abstract: Release from arrest in G2 phase of the cell cycle causes profound changes in rat ether-à-go-go (r-eag) K+ channels heterologously expressed in Xenopus oocytes. The most evident consequence of the onset of maturation is the appearance of rectification in the r-eag current. The trigger for these changes is located downstream of the activation of mitosis-promoting factor (MPF). We demonstrate here that the rectification is due to a voltage-dependent block by intracellular Na+ ions. Manipulation of the intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 44 publications
6
96
1
2
Order By: Relevance
“…In addition, cell cycle regulation of exogenously expressed channel proteins in Xenopus oocytes has been reported. The rat ether-a-go-go K ϩ channel alters its voltage dependence during meiotic maturation through an MPF-mediated process (32). However, to our knowledge, none of these currents exhibit a similar regulation to the rapid and complete inactivation observed for SOCE.…”
Section: Resultsmentioning
confidence: 84%
“…In addition, cell cycle regulation of exogenously expressed channel proteins in Xenopus oocytes has been reported. The rat ether-a-go-go K ϩ channel alters its voltage dependence during meiotic maturation through an MPF-mediated process (32). However, to our knowledge, none of these currents exhibit a similar regulation to the rapid and complete inactivation observed for SOCE.…”
Section: Resultsmentioning
confidence: 84%
“…As such, ion channel expression and function may vary depending on the cell cycle phase. For example, a previous study demonstrated that EAG1 expression is dependent on the cell cycle in human neuroblastoma cells (Meyer and Heinemann 1998), and a heterologous expression study in Xenopus oocytes has demonstrated changes in the electrophysiological properties of rat Eag1 that depend on the mitosis-promoting factor (Pardo et al 1998). Similarly, the expression and voltage dependence of HERG channel activation differ during the cell cycle, which may reflect another venue for dynamic regulation of cell proliferation (Arcangeli et al 1995;Crociani et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…1 was used. Since rectification can be attributed to block by intracellular sodium (Pardo et al 1998), it can (and does) vary from oocyte to oocyte. Fitting the parameters of Eq.…”
Section: Current-voltage Relationship In the Absence Of External Magnmentioning
confidence: 99%